PENGARUH DUE PROFESSIONAL CARE, AKUNTABILITAS, DAN TIME BUDGET PRESSURE TERHADAP KUALITAS AUDIT - Cholifa, Saydah (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This main aims of this study is to test whether Due Professional Care, Accountability, and Time Budget Pressure affect the Audit quality. The sample collection technique has been carried out by using purposive sampling. The result of the research shows that there is a variable due professional care, accountability, and time budget variables are used by the researcher is when the level of due professional care, accountability, and time budget pressure which is owned by an auditor is getting high therefore the audit quality which is generated by the auditor is getting better as well.Keywords: Due Professional Care, Accountability, Time Budget Pressure, and Audit Quality